Differential Lipid Response to Statins Is Associated With Variants in the BUD13–APOA5 Gene Region. Issue 2 (August 2015) - O'Brien, Sarah E.; Schrodi, Steven J.; Ye, Zhan; Brilliant, Murray H.; Virani, Salim S.; Brautbar, Ariel
Abstract : Abstract: Genetic variants within the BUD13–APOA5 gene region are known to be associated with high-density lipoprotein cholesterol (HDL-C) and triglyceride (TG) levels. Recent studies suggest that single nucleotide polymorphisms (SNPs) within this region affect HDL-C response to statin–fibrate combination therapy and low-density lipoprotein cholesterol (LDL-C) response to statin therapy. We hypothesized that SNPs within the BUD13–APOA5 region are associated with TG, HDL-C, and LDL-C response to statin therapy. We examined 1520 observations for 1086 patients from the Personalized Medicine Research Project, a large biorepository at the Marshfield Clinic Research Foundation, who had received statin therapy and been previously genotyped for polymorphisms in the 11q23 chromosomal region. A significant differential response to statin therapy was observed for 3 SNPs. The minor allele at rs11605293 significantly attenuated TG-lowering response to pravastatin ( P = 0.000159), whereas the minor allele at rs12806755 was associated with a similar response to lovastatin ( P = 0.000192). Genotypes at rs947990 significantly attenuated LDL-C reduction to atorvastatin therapy ( P = 0.000668) with some patients with the minor allele having LDL-C increase after therapy. No SNPs within the BUD13–APOA5 region were associated with a significant effect on HDL-C reduction in response to statin therapy. In conclusion, this study suggests that common SNPs within the BUD13–APOA5 can affect TG and LDL-C response to statin therapy in a North American population. Abstract : Supplemental Digital Content is Available in the Text.